Movement instruction during copying activities with beginning writers - Muñoz-Abrines, María Loreto (2020)
This article aims to review theoretical and empirical support to help rethink the pedagogical practices being used with novice writers to encourage the process of automation of graphomotor skills during copying activities. This is because this activity is necessary to develop graphomotor skills and, consequently, for the automation process; mechanical, repeated and unconscious copying is inefficient and counterproductive. Not only does it not contribute to the construction of muscular memory, a key aspect for the automation of the layout, but the demands transcend the motor capacities of childhood. It is concluded that in order for copying practices to be respectful of these motor capacities and to contribute to the automation of graphomotor skills, they should be focused on the construction of muscle memory by means of movement instruction using large print.